2023
DOI: 10.3390/en16041876
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Electrocatalysts for Advanced Applications in Fuel Cells

Abstract: Nanostructured materials have gained much attention in recent engineering and material- science research due to their unique structural makeup, which stands them out from their bulk counterparts. Their novel properties of tiny-size structural elements (molecules or crystallites, clusters) of nanoscale dimensions (1 to 100 nm) make them a perfect material for energy applications. The recent keen interest in nanostructured materials research by academia and industrial experts arises from the unique variable char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 103 publications
0
7
0
Order By: Relevance
“…This happens because a nanostructured material undergoes a transition process from an infinitely extended solid to a particle containing a definable number of atoms. [ 79 ] It has been reported that SOFC performance has a close correlation with electrode microstructure. [ 80 ]…”
Section: Role Of Nanomaterials In Sofcmentioning
confidence: 99%
“…This happens because a nanostructured material undergoes a transition process from an infinitely extended solid to a particle containing a definable number of atoms. [ 79 ] It has been reported that SOFC performance has a close correlation with electrode microstructure. [ 80 ]…”
Section: Role Of Nanomaterials In Sofcmentioning
confidence: 99%
“…The main and primary demand in the present society is an uninterrupted power supply which can come from various sources like coal, petroleum, nuclear, solar, and wind [3,4]. Conventional fossil fuels will power this substantial human population for another 50 years [5,6]. However, to meet this enormous energy demand, fossil fuels have reached the brink of extinction and emit harmful gases, especially greenhouse gas (GHG) [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Each year, 50 billion tons of CO 2 is emitted on the planet. 2,3 Because of their low greenhouse gas emissions and high capacity factor, high-temperature PEMFCs have been expansively studied as green energy alternatives. [4][5][6][7]63,64 The development of alternative energy sources and the advancement of currently used electrochemical systems (such as fuel cells) for the production of electrical energy would both benefit greatly from advanced research into nanostructured materials.…”
Section: Introductionmentioning
confidence: 99%
“…At present, oil is the most important source of energy consumed in the world. Because of the continuous release of hazardous chemicals into the atmosphere caused by the use of nonrenewable energy sources, environmental experts are extremely concerned about global warming . Carbon dioxide equivalents (CO 2 ) are used to monitor greenhouse gases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation